Asupan gizi dan status gizi vegetarian pada komunitas vegetarian di Yogyakarta - Lusia Anggraini; Wiryatun Lestariana; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2015)
Background: Vegetarian diet has become a popular diet among people. The information about the benefits of going plant-based as opposed to the risks of degenerative illnesses is widespread and publicly eligible. However, the diet is known to cause the lack of some nutrients such as protein, iron, and B12, which has the implication on one's nutritional status.Objective: The study is aimed at identifying nutrient intake and nutritional status vegetarians and the influential factors among vegetarians in Yogyakarta.Method: The study is an observational one with a cross sectional design. It is conducted on vegetarians living in Yogyakarta, which, as methodologically required, involves 102 respondents. The nutritional intake is measured through Food Frequency Questionnaire (FFQ), and the nutritional status through the Body Mass Index status, ferritin serum level, protein serum level and hemoglobin level. The data are analysed using chi square and multiple logistic regression.Results: The mean intake of energy, fat, zinc, vitamin B6, and vitamin B12 is higher in lactoovo vegetarian while vegan is the higher intake of carbohydrates, protein, iron, folic acid, and vitamin C. Some nutritional intake of less than 80% of AKG is the intake of energy, carbohydrates, zinc, folic acid, and vitamin B12. There are significant differences of the intakes of vitamin B12 between both groups. The vegan’s IMT is lower than lactoovo vegetarian. Lactoovo vegetarian’s protein serum levels are higher, however serum levels of vegan’s ferritin and hemoglobin are higher. There are significant differences in serum levels of protein and hemoglobin levels in both groups. There is a significant relation between the intake of iron and hemoglobin levels in vegetarians.Conclusion: Lactoovo vegetarian diet and vegan diet can fulfill the nutritional adequacy, but the things that need to keep in mind are the quality and quantity of food and a good diet plan in order to comply all the nutritional adequacy especially food sources of zinc, folic acid, and vitamin B12.